Reposisi Jamaah Tarekat dalam Dinamika Dakwah Kontemporer: Studi Kasus Tarekat Khalwatiyah Zamman di Kabupaten Wajo, Sulawesi Selatan - Nurhikmah, Nurhikmah ``; K., Abd. Halim; Azis, Aminah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
This article aims to discussed the Khalwatiyah Zamman in Wajo Regency, South Sulawesi. The concept of Da'wa and the form of the practice of the teachings of the Khalwatiyah Zamman in Wajo Regency was formed by the strategy of Da'wa ; the Khalifah (teachers) in the Khalwatiyah school, the Baiat which became the member in Khalwatiyah, the Zikir done consistently and the figure used as guidance. The supporting factors of Khalwatiyah because the city of Sengkang where the dominant of Khalifah Puang Lompo who is the old man of the Khalifah in Patte'ne whose existence is supported by the government and all descendants of the Khalifah and its followers. The inhibition of its existence does not move structurally organizational so that Khalwatiyah in Wajo developed naturally from the descendants and some of the sympathizers who eventually became followers in the teachings of the Khalwatiyah of Wajo Regency.